Calculated globulin can be used as a screening test for antibody deficiency in children and adolescents - Frias Sartorelli de Toledo Piza, Cristina; Aranda, Carolina Sanchez; Solé, Dirceu; Jolles, Stephen; Condino-Neto, Antonio (Frontiers in Immunology, 2024)
Purpose Calculated globulin (CG, total protein minus albumin levels) correlate well with IgG levels and has been proposed as a suitable screening method for individuals with primary antibody deficiencies (PADs). We aimed to show the correlation of CG with IgG levels in children and adolescents, utilizing a common method for albumin measurement, bromocresol green. Methods Individuals from two Allergy and Immunology clinics were invited to participate. Inclusion criteria were age < 18, stable conditions, and signed informed consent. We included 1084 individuals. Immunoglobulin G values were determined by immunoturbidimetry; the colorimetric bromocresol green method and the Architect Biuret method were utilized for the albumin and total protein (TP) measurements, respectively. Results A total of 1084 individuals were included in the analysis and divided into 4 age groups (0 to <1 year, 1 to <4 years, 4 to <10 years, and 10 to <18 years). For all patients, the mean age was 6.1 (± 5) years old, the mean IgG was 9.4 (± 4.7) g/L, and CG was 23.7 (± 5.9) g/L. The most frequent diagnosis were respiratory allergies, followed by inborn errors of immunity. IgG and CG varied according to age group. Cutoff values for hypogammaglobulinemia varied from 13.8 g/L in children < 1 year to 23.1 g/L in children and adolescents aged 10 to <18 years. CG sensitivity varied from 70.9% in children aged 1 to <4 years old to 95.8% in children 4 to <10. Specificity ranged from 87.5% in children 4 to <10 years old to 100% in children and adolescents aged 10 to <18 years. Conclusion CG is a suitable screening test for hypogammaglobulinemia in children less than 18 years of age.